A high-performance n-butanol gas sensor based on ZnO nanoparticles synthesized by a low-temperature solvothermal route1. Issue 67 (24th July 2015) - Liu, Xu; Chen, Nan; Xing, Xinxin; Li, Yuxiu; Xiao, Xuechun; Wang, Yude; Djerdj, Igor
<x xml:space="preserve">Abstract</x> Solvothermally synthesized ZnO nanoparticles applied as a sensing layer for an n-butanol gas sensor show a very good gas response performance.